Pengaruh Pembiayaan Akad Musyarakah terhadap Profitabilitas Bank Syariah di Indonesia - Selfiana Dewi; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
According to current trends, there is a need for Islamic banks both in quantity and quality. Customers will think about and choose Islamic banks more often as quality improves. The quality of Islamic banks can be improved by looking at their performance and sustainability capabilities which are influenced by the quality of funding or investment. This sharia bank, which was founded by considering these two types of financing, uses sharia banking as its financing fund distribution product. These banks finance transactions with the aim of making money. based on the results of collaborative projects implemented based on musyarakah agreements and profit sharing principles. Musyarakah financing is a collaborative effort between capital owners to run a particular business in accordance with sharia principles, with both parties participating in the success of the business. parties according to predetermined ratios, and losses are allocated according to capital advice. In the financial industry, bank performance is one of the main indicators of health. One method for evaluating bank operations is to use metrics to measure profitability, which is usually called ROA or profit assets. ROA is a capability metric; a business makes money by using all its resources and skills. A bank will make more money and have a better asset utilization position if its return on assets (ROA) is higher. In other words, ROA can show how effectively managers allocate resources to generate profits.